Assessment of intensive care unit‐acquired weakness in young and old mice: An E. coli septic peritonitis model. Issue 1 (21st November 2015) - Witteveen, Esther; Hoogland, Inge C.M.; Wieske, Luuk; Weber, Nina C.; Verhamme, Camiel; Schultz, Marcus J.; van Schaik, Ivo N.; Horn, Janneke
ABSTRACT: Introduction : There are few reports of in vivo muscle strength measurements in animal models of ICU‐acquired weakness (ICU‐AW). In this study we investigated whether the Escherichia coli ( E. coli ) septic peritonitis mouse model may serve as an ICU‐AW model using in vivo strength measurements and myosin/actin assays, and whether development of ICU‐AW is age‐dependent in this model. Methods : Young and old mice were injected intraperitoneally with E. coli and treated with ceftriaxone. Forelimb grip strength was measured at multiple time points, and the myosin/actin ratio in muscle was determined. Results : E. coli administration was not associated with grip strength decrease, neither in young nor in old mice. In old mice, the myosin/actin ratio was lower in E. coli mice at t = 48 h and higher at t = 72 h compared with controls. Conclusions : This E. coli septic peritonitis mouse model did not induce decreased grip strength. In its current form, it seems unsuitable as a model for ICU‐AW. Muscle Nerve 53 : 127–133, 2016